Melorheostosis: A Retrospective Clinical Analysis of 24 Patients at the Mayo Clinic. Issue 3 (30th July 2016) - Smith, Gabriel C.; Pingree, Matthew J.; Freeman, Laura A.; Matsumoto, Jane M.; Howe, Benjamin M.; Kannas, Stephanie N.; Pyfferoen, Mary D.; Struss, Leah T.; Wenger, Doris E.; Amrami, Kimberly K.; Matsumoto, Martha; Jurisson, Mary L.
Abstract: Background: Current understanding of the clinical features of persons with melorheostosis is restricted primarily to individual case reports and small case series. Objective: To assess the clinical features of patients with melorheostosis treated at our institution from 1972 through 2010. Design: Chart review. Setting: Tertiary academic medical center. Participants: Twenty‐three patients with "definite" and one patient with "probable" melorheostosis based on radiographic criteria. Methods: The eligible study cohort was identified through the Rochester Medical Index database. Further diagnostic confirmation of patients with melorheostosis was performed by radiographic review. Main Outcome Measurements: We evaluated age at first visit to our institution, gender, affected body area, number of bones affected, presenting symptoms, surgical evaluation, and therapies provided. Results: The average age at first evaluation at our clinic was 36.5 years (median 41.5 years, range 3‐68 years). The female to male ratio was 4:1. The lower extremity was most commonly affected (66.6%), followed by upper extremity (33.3%), spine (16.6%), and head (8.3%). One‐third of patients had involvement of a single bone; two‐thirds had multiple bone involvement. Pain was the most common presenting concern (83.3%), followed by deformity (54.1%), limitation of movement (45.8%), numbness (37.5%), and weakness (25.0%). Most patients had a physician evaluation (87.5%); patients also underwent orthopedic surgery (45.8%), physical therapy (33.3%), and occupational therapy (12.5%). Conclusions: Melorheostosis is a rare sclerotic bone disease resulting in pain, deformity, and dysfunction. An interdisciplinary approach to care should include nonoperative and operative evaluation, as well as appropriate therapies. A prospective approach to evaluation, including imaging and physical examinations, would provide valuable longitudinal data. Level of Evidence: IV